Aging, Osteocytes, and Mechanotransduction - Hemmatian, Haniyeh (Curr Osteoporos Rep, 2017)
PURPOSE OF REVIEW: The bone is able to adapt its structure to mechanical signals via the bone remodeling process governed by mechanosensitive osteocytes. With aging, an imbalance in bone remodeling results in osteoporosis. In this review, we hypothesized that changes in lacunar morphology underlie the decreased bone mechanoresponsiveness to mechanical loading with aging. RECENT FINDINGS: Several studies have reported considerable variations in the shape of osteocytes and their lacunae with aging. Since osteocytes can sense matrix strain directly via their cell bodies, the variations in osteocyte morphology may cause changes in osteocyte mechanosensitivity. As a consequence, the load-adaptive response of osteocytes may change with aging, even when mechanical loading would remain unchanged. SUMMARY: Though extensive quantitative data is lacking, evidence exists that the osteocyte lacunae are becoming smaller and more spherical with aging. Future dedicated studies might reveal whether these changes would affect osteocyte mechanosensation and the subsequent biological response, and whether this is (one of) the pathways involved in age-related bone loss.